Transcriptional Regulation of the Two Sterol Esterification Genes in the Yeast Saccharomyces cerevisiae - Jensen-Pergakes, Kristen (American Society for Microbiology, 2001)
Saccharomyces cerevisiae transcribes two genes, ARE1 and ARE2, that contribute disproportionately to the esterification of sterols. Are2p is the major enzyme isoform in a wild-type cell growing aerobically. This likely results from a combination of differential transcription initiation and transcript stability. By using ARE1 and ARE2 promoter fusions to lacZ reporters, we demonstrated that transcriptional initiation from the ARE1 promoter is significantly reduced compared to that from the ARE2 promoter. Furthermore, the half-life of the ARE2 mRNA is approximately 12 times as long as that of the ARE1 transcript. We present evidence that the primary role of the minor sterol esterification isoform encoded by ARE1 is to esterify sterol intermediates, whereas the role of the ARE2 enzyme is to esterify ergosterol, the end product of the pathway. Accordingly, the ARE1 promoter is upregulated in strains that accumulate ergosterol precursors. Furthermore, ARE1 and ARE2 are oppositely regulated by heme. Under heme-deficient growth conditions, ARE1 was upregulated fivefold while ARE2 was down-regulated. ARE2 requires the HAP1 transcription factor for optimal expression, and both ARE genes are derepressed in a rox1 (repressor of oxygen) mutant genetic background. We further report that the ARE genes are not subject to end product inhibition; neither ARE1 nor ARE2 transcription is altered in an are mutant background, nor does overexpression of either ARE gene alter the response of the ARE-lacZ reporter constructs. Our observations are consistent with an important physiological role for Are1p during anaerobic growth when heme is limiting and sterol precursors may accumulate. Conversely, Are2p is optimally required during aerobiosis when ergosterol is plentiful.